Mechanical and thermal performance of polylactic Acid (PLA)- Saba banana peel composite - Ahmad Irfan Nazarudin; Adi Azriff Basri; Ernnie Illyani Basri; Kamarul Arifin Ahmad; Mohammed Thariq Haji Hameed Sultan; Mohd Nor Faiz Norrahim; Mohd Rafein Zakaria (Journal of Materials Research and Technology)
Synthetic materials reinforced with natural fibers are attracting great attention of scientists and researchers. Sustainability and eco-friendly nature along with easy availability and low cost are the key reasons. In this work, a natural fiber such as banana peel powder was investigated to create composite materials while enhancing mechanical properties. The banana powder was extracted from banana peel waste by the drying method combined with grinding and sieving at 60 μm procedures followed by melt-blending and compression-moulding. Composite weightage was performed to exhibit powder with 0.5 %, 1 %, 2 % and 3 %. FTIR findings have indicated great compatibility and bonding between BPP and PLA. SEM and visual observations showed visual evidence that regular dispersion of BPP particles and provided toughening effect in 0.5 % and 1 % BPP composites. For compression moulding fabrication, 3251D PLA is found to have maximum tensile strength of 44.15 MPa and flexural strength of 36.18 MPa. Compared to PLA, flexibility is improved by 72.99 %. The reported optimum powder concentration was 1 % BPP used for the material polylactic acid (PLA/BPP) composite gave good results and the mechanical strength values were kept at the specified level (tensile strength: 37.45 MPa flexural strength: 70.51 MPa, and yield strength: 171.66 J/m). Thermogravimetric analysis indicated that the PLA-reinforced blend exhibits greater thermal stability compared to neat PLA and is supported with slight decreased temperature in DSC tests.